Signalling cross talk of the HIF system: involvement of the FIH protein. - Coleman, M; Ratcliffe, P (2009)
Cellular and systemic oxygen homeostasis is regulated by an oxygen-sensitive signalling pathway centred on a transcription factor known as Hypoxia Inducible Factor (HIF). Regulation of HIF activity and protein stability is mediated by a family of hydroxylases that act as oxygen sensors due to the dependence of the hydroxylation reaction on oxygen. The transcriptional activity of HIF is at least in part determined by asparaginyl hydroxylation by Factor Inhibiting HIF (FIH) of a C-terminal residue that regulates co-activator recruitment. The activity of FIH on HIF is limiting; emerging data suggest this may be due to competition from a large family of alternative FIH substrates that act as a 'sink' for FIH activity. These alternative substrates are targeted for hydroxylation at conserved Asn residues within a protein interaction domain known as the Ankyrin Repeat Domain (ARD). Many ARD-containing proteins bind to FIH more tightly than does HIF. Furthermore, ARD proteins are common within the proteome and in some cases are highly abundant. Since ARD substrates bind to FIH in a similar manner to HIF it is thought that these properties of the ARD family lead to competitive inhibition of FIH-dependent HIF hydroxylation. We summarise the current literature here and discuss the possible role of cross-talk between the FIH, HIF and ARD systems in fine tuning hypoxia responses.